Mexican Pointy Boots and the Tribal Scene: Global Appropriations of Local Cultural Practices in the Virtual Age - Helena Simonett; César Burgos Dávila (Transatlantica)
In this essay, we examine music and its performative power by engaging in issues such as the localization of global cultural practices, the embracing of cultural practices based on a shared sense of marginalization and peripheralization, as well as the appropriation and resignification of “odd” cultural practices for global consumption, resulting in a cultural mutation of such practices and their objects from “low” to “art.” Our approach to analyze música tribal, a specific type of Mexican “tribal” electronic dance music that partially originated in Monterrey cumbia and, correspondingly, appealed to youths situated outside the mainstream, is to understand musical practices as related to the re-territorialization of foreign cultural practices that give a voice of social legitimacy to historically marginalized individuals.